Development of a multiplex assay to determine the expression of mitochondrial genes in human skeletal muscle. Issue 8 (19th May 2021) - Aird, Tom P.; Farquharson, Andrew J.; Drew, Janice E.; Carson, Brian P.
Abstract : New Findings: What is the central question of this study? Can a custom‐designed multiplex gene expression assay be used to quantify expression levels of a targeted group of mitochondrial genes in human skeletal muscle? What is the main finding and its importance? A custom‐designed GeXP multiplex assay was developed, and the ability to accurately quantify expression of a targeted set of mitochondrial genes in human skeletal muscle was demonstrated. It holds distinct methodological and practical advantages over other commonly used quantification methods. Abstract: Skeletal muscle is an important endocrine tissue demonstrating plasticity in response to external stimuli, including exercise and nutrition. Mitochondrial biogenesis is a common hallmark of adaptations to aerobic exercise training. Furthermore, altered expression of several genes implicated in the regulation of mitochondrial biogenesis, substrate oxidation and nicotinamide adenine dinucleotide (NAD + ) biosynthesis following acute exercise underpins longer‐term muscle metabolic adaptations. Gene expression is typically measured using real‐time quantitative PCR platforms. However, interest has developed in the design of multiplex gene expression assays (GeXP) using the GenomeLab GeXP™ genetic analysis system, which can simultaneously quantify gene expression of multiple targets, holding distinct advantages in terms of throughput, limiting technical error, cost effectiveness, and quantifying gene co‐expression. This study describes the development of a custom‐designed GeXP assay incorporating the measurement of proposed regulators of mitochondrial biogenesis, substrate oxidation, and NAD + biosynthetic capacity in human skeletal muscle and characterises the resting gene expression (overnight fasted and non‐exercised) signature within a group of young, healthy, recreationally active males. The design of GeXP‐based assays provides the capacity to more accurately characterise the regulation of a targeted group of genes with specific regulatory functions, a potentially advantageous development for future investigations of the regulation of muscle metabolism by exercise and/or nutrition. Abstract :